Detailed preliminary information on confirmed cases of COVID-19 (Revised), Public Health Agency of Canada - Statistics Canada (Government of Canada, 2020)
In collaboration with the Public Health Agency of Canada (PHAC), this table provides Canadians and researchers with preliminary data to monitor only the confirmed cases of coronavirus (COVID-19) in Canada. Given the rapidly-evolving nature of this situation, these data are considered preliminary.